1991
DOI: 10.1111/j.1708-8240.1991.tb00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effects of Application of a Citroxain‐Containing Dentifrice

Abstract: The benefits to the patient of the removal of tooth deposits is well documented. Should such removal provide the additional effect of “whitening” the tooth surface, an additional cosmetic benefit would be provided. This study documents that a Citroxain‐containing dentifrice provides all of these benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…The present study showed that the mean Lightness value of test group after brushing was significantly higher than that of the control group. Similar results were reported by Lyon Jr (1991) (12) with Citroxain (mixture of papaya, alumina and sodium citrate) containing dentifrice (Rembrandt) using a customized shade guide. The test dentifrice in the present study contained extracts of papain and bromelain, which are proteolytic enzymes.…”
Section: Discussionsupporting
confidence: 85%
“…The present study showed that the mean Lightness value of test group after brushing was significantly higher than that of the control group. Similar results were reported by Lyon Jr (1991) (12) with Citroxain (mixture of papaya, alumina and sodium citrate) containing dentifrice (Rembrandt) using a customized shade guide. The test dentifrice in the present study contained extracts of papain and bromelain, which are proteolytic enzymes.…”
Section: Discussionsupporting
confidence: 85%
“…Clinical studies using toothpaste containing a mixture of papain, alumina and sodium citrate (Rembrandt) have also reported a significant stain removal. [7–9] The test dentifrice in the present study contained extracts of papain and bromelain, which are proteolytic enzymes. They disrupt and ⁄ or remove the protein portion of the pellicle ⁄ plaque layer that forms on the surface of teeth over time, thus removing the stains that are bound to these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Clinical studies have demonstrated the stain removal efficacy of dentifrice containing papain, alumina and sodium citrate. [7–9] Recently an in vitro study reported that a papain and bromelain (proteolytic enzymes) containing dentifrice was more effective in removing stains than the control dentifrice. [10]…”
Section: Introductionmentioning
confidence: 99%
“…81 More recently, a toothpaste containing a mixture of the protease enzyme papain, alumina and sodium citrate has been described in the literature. Although an early clinical study showed no significant effect of this toothpaste on removing established extrinsic stain versus a placebo toothpaste, 82 further clinical studies have demonstrated the combination toothpaste to be effective at removing established stains, 83 more effective at removing established extrinsic stain than a tartar control toothpaste, 84 and more effective at removing chlorhexidine induced stain than a control toothpaste. 85 Phosphate materials, such as pyrophosphate, tripolyphosphate and hexametaphosphate, tend to have a strong binding affinity for enamel, dentine and tartar, and during adsorption they have been shown to desorb stain components.…”
Section: Abrasivesmentioning
confidence: 94%